The apprentice's masterpiece : a story of medieval Spain - Little, Melanie, 1969- (New York : Annick Press, 2009)
Presents brief narrative poems set in fifteenth-century Spain, when apprentice scribe Ramon witnesses the atrocities of the Inquisitions while Amir, born a Muslim and forced to give up his faith, is taken in by Ramon's family of Jews who were forced to convert to Christianity.
Resource Links.
School Library Journal.
Voice of Youth Advocates (V.O.Y.A.).
Young Adult
Keywords: Inquisition -- Spain -- Juvenile fiction; Scribes -- Juvenile fiction; Historical fiction; Inquisition -- Fiction; Scribes -- Fiction; Historical fiction; Inquisition -- Fiction; Scribes -- Fiction; Spain -- Fiction; Spain -- Fiction; Historical fiction